PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS H5P BERMUATAN STRATEGI HEURISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH DALAM MATERI BENTUK ALJABAR KELAS VII SMPN 10 SUNGAI KAKAP - Nunuk Parwati; Yudi Darma; Utin Desy Susiaty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to produce H5P-based instructional media incorporating heuristic strategies that achieve validity, practicality, and effectiveness in improving students' mathematical problem-solving abilities on algebraic expressions in Grade VII at SMPN 10 Sungai Kakap. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate). The research subjects consisted of 23 seventh-grade students. The instruments used in this study included expert validation sheets, teacher response questionnaires, student response questionnaires, and a post-test. The results showed that the validity level of the instructional media, based on expert assessments, obtained an average percentage of 86.67%, categorized as very valid. The practicality level, based on teacher and student response questionnaires, obtained an average percentage of 91.25%, categorized as very practical. Meanwhile, the effectiveness of the media based on students’ post-test results showed a classical completeness rate of 85.71%, categorized as effective. Thus, the H5P-based instructional media with heuristic strategies is declared feasible and effective for use in the mathematics learning process.